Gut Microbial Diversity Assessment of Indian Type-2-Diabetics Reveals Alterations in Eubacteria, Archaea, and Eukaryotes - Bhute, Shrikant S.; Suryavanshi, Mangesh V.; Joshi, Suyog M.; Yajnik, Chittaranjan S.; Shouche, Yogesh S.; Ghaskadbi, Saroj S. (Frontiers in Microbiology, 2017)
Diabetes in India has distinct genetic, nutritional, developmental and socio-economic aspects; owing to the fact that changes in gut microbiota are associated with diabetes, we employed semiconductor-based sequencing to characterize gut microbiota of diabetic subjects from this region. We suggest consolidated dysbiosis of eubacterial, archaeal and eukaryotic components in the gut microbiota of newly diagnosed (New-DMs) and long-standing diabetic subjects (Known-DMs) compared to healthy subjects (NGTs). Increased abundance of phylum Firmicutes (p=0.010) and Operational Taxonomic Units (OTUs) of Lactobacillus (p<0.01) were observed in Known-DMs subjects along with the concomitant graded decrease in butyrate-producing bacterial families like Ruminococcaceae and Lachnospiraceae. Eukaryotes and fungi were the least affected components in these subjects but archaea, except Methanobrevibacter were significantly decreased in them. The two dominant archaea viz. Methanobrevibacater and Methanosphaera followed opposite trends in abundance from NGTs to Known-DMs subjects. There was a substantial reduction in eubacteria, with a noticeable decrease in Bacteroidetes phylum (p=0.098) and an increased abundance of fungi in New-DMs subjects. Likewise, opportunistic fungal pathogens such as Aspergillus, Candida were found to be enriched in New-DMs subjects. Analysis of eubacterial interaction network revealed disease-state specific patterns of ecological interactions, suggesting the distinct behaviour of individual components of eubacteria in response to the disease. PERMANOVA test indicated that the eubacterial component was associated with diabetes-related risk factors like high triglyceride (p=0.05), low HDL (p=0.03), and waist-to-hip ratio (p=0.02). Metagenomic imputation of eubacteria depict deficiencies of various essential functions such as carbohydrate metabolism, amino acid metabolism etc. in New-DMs subjects. Results presented here shows that in diabetes, microbial dysbiosis may not be just limited to eubacteria. Due to the inter-linked metabolic interactions among the eubacteria, archaea and eukarya in the gut, it may extend into other two domains leading to trans-domain dysbiosis in microbiota. Our results thus contribute to and expand the identification of biomarkers in diabetes.